D–π–A-type fluorinated tolanes with a diphenylamino group: crystal polymorphism formation and photophysical behavior. Issue 5 (19th January 2022) - Yamada, Shigeyuki; Kobayashi, Kazuki; Morita, Masato; Konno, Tsutomu
Abstract : Ph2 N-Substituted fluorinated tolanes produced two polymorphisms, which display a distinct photoluminescence behavior; one polymorphism showed green PL and the other exhibited yellow PL. Abstract : Novel D–π–A-type fluorinated tolane with a diphenylamino group was synthesized, yielding two crystal polymorphisms induced by fluorine atoms in the tolane scaffold. The two crystal polymorphisms exhibited distinct photophysical behavior, with one displaying a significant photoluminescence behavior change upon the application of external stimuli.